Implementing TPACK Framewok in English Language Teaching - Tiara Savitri; Audi Yundayani; Wisma Yunita (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to identify and describe the implementation of TPACK Framework in English Language Teaching in SMPN 4 Tanjungpandan, Belitung, Kepulauan Bangka Belitung. The research is a qualitative study. The participants of this research consisted of two English teachers from SMPN 4 Tanjungpandan and the students of nineth grade. Data collection techniques are observation, interviews, and documentation. Technological Pedagogical Content Knowledge (TPACK) is a framework for understanding the varied forms of knowledge necessitated by EFL teachers to integrate ICT in their teaching. The results of this study indicate that implementing TPACK framework in Englis classroom gives positive impact to the learning achievements both the teachers and the students. By integrating technology learning applications such as World Wall, You Tube apps, the learning process becomes interesting and enjoyable. The participation of the students increases significantly. In the future, TPACK Framework takes part in increasing the quality English Language Teaching in Indonesia.